The Comparative Study of the Olympics between the West and East - Qiang, Wang (Universitas Pendidikan Indonesia, 2025)
This paper employs a comparative analysis to explore the different manifestations of the Olympic movement within Chinese and Western cultures and the cultural factors behind them. It begins by reviewing the historical origins of the Olympic movement, emphasizing its role as an international sporting event that showcases not only athletic competition but also cultural exchange. The paper then focuses on the embodiment of the Olympic spirit within Western culture, contrasting it with an in-depth discussion of China's acceptance and localization of the Olympic movement. In China, the Olympics are not only a display of athletic competition but also a representation of national image and cultural soft power. Furthermore, the paper discusses the different modes of participation and attitudes towards the Olympic movement in Chinese and Western societies and how these differences affect the global development of the Olympic movement. Western societies tend to view the Olympics as a symbol of individual achievement and national pride, while China places greater emphasis on collective honour and national pride. Finally, the paper suggests ways to better integrate Chinese and Western cultures to promote the diverse development of the Olympic movement and to maintain and pass on the Olympic spirit in the context of globalization.